PERFORMANCE TEST OF THE AIR-COOLED CHILLER SYSTEM USING HCR 134a REFRIGERANT IN CONDENSER OUTPUT TEMPERATURE 30°C - Arozi, Moh (TRAKSI, 2024)
This experimental test aims to determine the effect of increasing the output temperature from the evaporator (T1) on a constant output temperature from the condenser (T3) on the performance of the piston hermetic compressor in the Air-Cooled Chiller vapor compression system, namely compressor power, refrigeration capacity and Coefficient of Performance (COP). ). This test uses HCR-134a as the main refrigerant and water as the secondary refrigerant. Data collection was carried out at the output temperature from the condenser (T3) = 300C with variations in the output temperature from the evaporator, namely -40C to 100C. Information recorded at each stage of the experiment includes temperature and pressure at the outlet of the evaporator, compressor and condenser, as well as voltage, electric current and refrigerant flow rate. The instruments and equipment used are an Air-Cooled Chiller with a piston hermetic compressor as the main test tool, a digital thermometer and alcohol thermometer as a temperature gauge, a high pressure gauge and a low pressure gauge as a pressure gauge and an orifice as a refrigerant flow rate gauge and a digital multimeter as a meter. voltage and electric current. To find out the thermodynamic properties of the observation data, the refprop6 program is used by entering temperature and pressure variables. From these dynamic properties, by using the Excel program, entering the existing equations, the performance values of the reciprocating piston compressor are calculated. Test results show that with an increase in the cooling load as indicated by an increase in the evaporator exit temperature (T1) from -40C to 100C at a constant condenser exit temperature of 300C, the refrigeration capacity, compressor power and performance coefficient (COP) tend to increase.